Benefits of Theatre at School for Children and Young People with Functional Diversity (Journal of Parents and Teachers, 2021)
Theatre as a motivating and transversal (in the sense of involving or dealing with contents from different fields, linking them together) pedagogical resource invites pupils/students with functional diversity to explore their talents and capabilities, giving them the opportunity to acquire competencies that would be difficult to achieve from the teacher’s desk. Strategies using drama become a valuable learning opportunity when used in classrooms with pupils/students with functional diversity. They offer the possibility of putting life skills into practice, thus complementing other, more instrumental learning. Each pupil/student will have the opportunity to break down and overcome his/her own barriers to communication and movement, reaching the heart of the audience through wonder and emotion.
Keywords: theatre and disability; artistic expression; functional diversity; communication; inclusion